al Lahjaat fii al Lughoh al ‘Arabiyah (Dirosah Tahliliyah ‘an Asbaab Ikhtilaaf al Lahjaat wa ‘Anaashiriha) - muflihah, Muflihah (Universitas Islam Negeri Raden Intan Lampung, 2018)
ABSTRAKDialect, according to many Arabic linguists, refers to language and letters used by a particular community that cause differences in the pronunciation even in the way particular letters are used among different societies.Dialect is variation in language depending on the users, that is the language as it is commonly used by the language users. Dialect; therefore, is dependent upon who use the language and where the users of the language reside. The geographical aspects shape the regional dialect and the social aspects shape the social dialect.This descriptive quantitative research aims to investigate the factors and aspects that shape some dialects in Arabic.The findings demonstrate that the factors influencing dialects include the geographical width of the area, the cross-language interaction and the different strata of the society.Keywords: Dialect, Arabic linguists, Causes and Elements